A maritime search and rescue location analysis considering multiple criteria, with simulated demand. Issue 1 (2nd January 2018) - Akbari, Amin; Eiselt, H. A.; Pelot, Ronald
ABSTRACT: In this paper, a multi-criteria analysis is performed on the location of Maritime Search and Rescue resources. Two well-known standard location models (the maximal covering location problem and p -median problem) are modified and applied in accordance with our problem characteristics. The study considers several distinct response vessel types with different capabilities. Future incidents are simulated based on the underlying distribution of historical incidents. The models are formulated and solved using data from the Atlantic region of Canada. The optimal solutions of these two models, along with the current resource arrangement, are compared in terms of five decision criteria: (1) mean access time, (2) primary coverage, (3) backup coverage, (4) Gini index and (5) maximum access time. The results indicate a significant increase in efficiency of resource utilization and availability of service based on access time and coverage criteria for the solutions provided by the optimization models compared to the current situation.